Reduced Plasmodium vivax Erythrocyte Infection in PNG Duffy-Negative Heterozygotes - Kasehagen, Laurin J. (Public Library of Science, 2007)
BACKGROUND: Erythrocyte Duffy blood group negativity reaches fixation in African populations where Plasmodium vivax (Pv) is uncommon. While it is known that Duffy-negative individuals are highly resistant to Pv erythrocyte infection, little is known regarding Pv susceptibility among heterozygous carriers of a Duffy-negative allele (+/−). Our limited knowledge of the selective advantages or disadvantages associated with this genotype constrains our understanding of the effect that interventions against Pv may have on the health of people living in malaria-endemic regions. METHODS AND FINDINGS: We conducted cross-sectional malaria prevalence surveys in Papua New Guinea (PNG), where we have previously identified a new Duffy-negative allele among individuals living in a region endemic for all four human malaria parasite species. We evaluated infection status by conventional blood smear light microscopy and semi-quantitative PCR-based strategies. Analysis of a longitudinal cohort constructed from our surveys showed that Duffy heterozygous (+/−) individuals were protected from Pv erythrocyte infection compared to those homozygous for wild-type alleles (+/+) (log-rank tests: LM, p = 0.049; PCR, p = 0.065). Evaluation of Pv parasitemia, determined by semi-quantitative PCR-based methods, was significantly lower in Duffy +/− vs. +/+ individuals (Mann-Whitney U: p = 0.023). Overall, we observed no association between susceptibility to P. falciparum erythrocyte infection and Duffy genotype. CONCLUSIONS: Our findings provide the first evidence that Duffy-negative heterozygosity reduces erythrocyte susceptibility to Pv infection. As this reduction was not associated with greater susceptibility to Pf malaria, our in vivo observations provide evidence that Pv-targeted control measures can be developed safely.